The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s2176-94512012000100007
|View full text |Cite
|
Sign up to set email alerts
|

The influence of asthma onset and severity on malocclusion prevalence in children and adolescents

Abstract: Objective: The influence of asthma, its severity levels and onset time on malocclusion occurrence were investigated. Methods: The sample was composed by 176 children/adolescents, of both genders, aged 3 to 15 years, that were divided in two groups. The asthma group (AG) enrolled 88 children/adolescents that were seen at the Breathe Londrina Program. The asthma-free group (AFG) enrolled 88 preschool and school children recruited in 2 public schools. Malocclusion diagnosis was made according to WHO criteria (OMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(19 reference statements)
2
4
0
Order By: Relevance
“…In addition, asthmatics usually develop mouth breathing habit owing to the frequent airway obstruction, especially during the episode of rhinitis or an acute asthmatic attack, which in turn would result in dehydration of the alveolar mucosa. [ 46 ] Furthermore, enhanced calcium level in the saliva of asthmatic children, as found in the present study, would favor more calculus deposition. [ 2 ] This increase in calcium level may be in response to beta-adrenergic bronchodilator drug such as the isoprenaline used as antiasthmatic drugs or may be even due to the pathological condition itself.…”
Section: Discussionsupporting
confidence: 57%
“…In addition, asthmatics usually develop mouth breathing habit owing to the frequent airway obstruction, especially during the episode of rhinitis or an acute asthmatic attack, which in turn would result in dehydration of the alveolar mucosa. [ 46 ] Furthermore, enhanced calcium level in the saliva of asthmatic children, as found in the present study, would favor more calculus deposition. [ 2 ] This increase in calcium level may be in response to beta-adrenergic bronchodilator drug such as the isoprenaline used as antiasthmatic drugs or may be even due to the pathological condition itself.…”
Section: Discussionsupporting
confidence: 57%
“…A direct relationship between malocclusion and asthma could not be established, corroborating with study findings with 176 children and adolescents between 3 and 15 years of age [20] but disagreeing with other investigations [5,21] that found more cases of crossed bites in asthmatic children and a relationship between asthma and anterior open bite in children [6]. Such findings, obtained from cross-sectional studies, reveal that there is no agreement in the dental literature regarding the relationship between the presence of malocclusion and asthma, its time of manifestation and the severity degree in the paediatric population [20].…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, the prompt diagnostic of the illness, as well as the establishment of a proper therapy could improve the symptoms and chronic complications of asthma and also reduce its adverse impact on craniofacial development. 5 The relationship between persistent bronchial asthma and dental caries incidence has been studied widely but with controversy results. However, a recent meta-analysis investigation has reported that caries incidence found almost doubled in asthmatic subjects both for primary and permanent dentition compared to that of the healthy control.…”
Section: Introductionmentioning
confidence: 99%